Critical success factors in e-learning / Asliaty Atim … [et al.] - Atim, Asliaty; Kiziltas, Ercan; Mahadi, Ilidina; Abdul Malik, Nurul Emilia Diyana (Akademi Pengajian Bahasa, 2021)
With the development of the Internet and Information, Communication Technology (ICT), many educational institutions offer a blended education along with face-to-face and online education. However, the Sars-Cov19 pandemic has made online education or e-learning compulsory in almost all educational institutions globally. This research has been designed to indicate the critical success factors for e learning. This case study focuses on an in-depth probing from students’ perspectives on the factors that affect the success of the course taught. It involved an IT course for undergraduates involving a 14-week learning about the theory and practical aspects of basic ICT skills. The researchers collected the data using a mixed-method approach via self-constructed questionnaire and semi-structured interview evaluating the students’ perspectives on their learning preference, participation and understanding in the course and the instructor’s technological skills, pedagogical strategies and subject competency in conducting the course. The findings include, the students have high agreement in wanting to learn despite Internet interruption or problems, students always interact with other students after class time and that there is a high agreement in the context of using their prior knowledge in e learning for this course and applying the knowledge learnt from the course into other courses. The researchers also found out that the majority of the students agree that the instructor has the knowledge of various online platforms and is able to use the skills to impart the subject content of the course to the students. The instructor also responds to their questions or queries even after the class ends and has a good content knowledge of the course and presents the content well.